2002
DOI: 10.3748/wjg.v8.i2.338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of progesterone on gastric emptying and intestinal transit in male rats

Abstract: AIM:To study the dose-dependent of progesterone (P) effect and the interaction between the oxytocin (OT) and P on gastrointestinal motility. METHODS:In order to monitor the gastric emptying and intestinal transit, the SD male rats were intubated via a catheter with normal saline (3ml/kg) containing Na 2 51 CrO 4 (0.5µ µ µ µ µCi/ml) and 10% charcoal. OT was dissolved into normal saline and P was dissolved into 75% alcohol.RESULTS: Low does of P (1mg/kg, i.p.) enhanced the gastric emptying (75±3%, P<0.05) and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 49 publications
1
35
2
4
Order By: Relevance
“…This study also demonstrated that E 2 and a combination of E 2 and progesterone inhibit gastric emptying, but progesterone alone enhances gastric emptying in Ovx rats (Chen et al 1995). Furthermore, in male rats, low-dose progesterone has been reported to increase gastric emptying, while high-dose progesterone inhibits it (Liu et al 2002). In this study, increased gastric emptying was seen in Ovx rats, as secretion of E 2 and progesterone was blocked due to ovariectomy.…”
Section: Discussionsupporting
confidence: 65%
“…This study also demonstrated that E 2 and a combination of E 2 and progesterone inhibit gastric emptying, but progesterone alone enhances gastric emptying in Ovx rats (Chen et al 1995). Furthermore, in male rats, low-dose progesterone has been reported to increase gastric emptying, while high-dose progesterone inhibits it (Liu et al 2002). In this study, increased gastric emptying was seen in Ovx rats, as secretion of E 2 and progesterone was blocked due to ovariectomy.…”
Section: Discussionsupporting
confidence: 65%
“…Bu sonuç, bizim metil selüloz boşalmasında artmış mide boşalması ile uyum içindedir. Buna karşın, OT'nin sıçanlarda ip verilmesi (0.8 mg/kg, bizim çalışmamızla aynı dozda) besin değeri olmayan sıvı gıdanın boşalmasını, çalış-mamızdaki kanüllü sıçanlarda olduğu gibi, inhibe etmiştir (31). Benzer şekilde, OT'nin anestezi altındaki sıçanlarda vagusun dorsal motor çekirdeğine uygulanması (4 pmol) mide motilitesini inhibe etmiştir (32).…”
Section: Discussionunclassified
“…Certains cas déjà décrits dans la littérature [6,7] ont lieu à la même période, d'autres plus tardivement à 33 SA ½ mais en lien avec une cause tumorale (adénocarci-nome du côlon droit) [8]. L'hypothèse d'un ralentissement de la motilité intestinale due à l'imprégnation hormonale progestéronique dès 12 SA est également à évoquer [9][10][11].…”
Section: Discussionunclassified